(untitled) (Medical Forum Monthly, 2026)
Objective: This was a prospective study to determine the impact of structured adjuvant oral care on clinical outcomes, such as duration of mechanical ventilation, ICU length of stay and mortality among mechanically ventilated ICU patients. Study Design: Randomized, controlled, trial studyPlace and Duration of Study: This study was conducted at the Intensive Care Unit of a Tertiary Care Hospital from 30 July 2024 and 3 January 2025. Methods: Mechanically ventilated patients (n = 100) were randomly put under intervention (n = 50) and control (n = 50) groups. The control group was provided with the standard care of the ICU in terms of oral care, whereas the intervention group went through the structured adjuvant oral care on top of the standard care. Clinical outcomes that were determined were the duration of mechanical ventilation, length of stay in ICU, and mortality. Independent sample t-tests and chi-square tests were used to analyze data with the statistical significance of p < 0.05. Results: The intervention group showed better clinical outcomes when compared to the control group. The average ICU stay was also significantly lower in the intervention arm (12.28; 7.15 days) than the control arm (16.57; 8.75 days; p= 0.009). On the same note, the average length of the mechanical ventilation duration was also significantly lower in the intervention group (11.19 ± 6.97 days) in comparison with the control group (15.46 ± 8.67 days; p = 0.008). The intervention group also had a lower mortality rate (44% vs. 66%). Conclusion: Organized oral care was linked with better clinical outcome among the patients who were put on mechanical ventilation in ICU. The intervention greatly decreased the mechanical ventilation duration and the length of stay in the ICU and was linked with a decreased mortality rate. The integration of systematic oral care procedures into the standard ICU nursing care could help to achieve better patient outcomes and less healthcare waste.